The Development of Differentiated Content Mathematics Learning Media Assisted by Websites with The RME Approach to Improve Mathematical Connection Ability - Azin Taufik; Nunu Nurhayati; Alif Dzikir Lestari (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2025)
Learning mathematics is often perceived as difficult, partly because instructional approaches often lack real-life relevance and do not adequately address the diverse needs and abilities of students, creating a gap in effective learning practices. This study aims to develop website-assisted mathematics learning media using the Realistic Mathematics Education (RME) approach for the topic of Three Variable Linear Equation System (SPLTV), intended to improve students’ mathematical connection skills. The media was created using Google Sites with a content differentiation strategy, adjusting material presentation based on students’ ability levels for more effective and meaningful learning. This Research and Development (R&D) study employed the Plomp model, consisting of three stages: introduction, development, and assessment. The research subjects were 24 tenth-grade students in the Industrial Electronics Engineering program at SMK Auto Matsuda. Data were collected through interviews, questionnaires, and pretest–posttest assessments, using instruments such as interview sheets, expert validation forms, practicality questionnaires, and mathematical connection tests. Validation results showed the media was highly valid, receiving scores of 91.1% from material experts and 85% from media experts. The test instrument was also proven valid and reliable (reliability = 0.89). Practicality scores indicated very good responses from teachers (90.2%) and students (94.58%). The media's effectiveness was demonstrated by a pretest score increase from 33.85 to 84.94 on the posttest, with an N-Gain of 0.78 (high category). These findings indicate that the developed media is not only feasible for classroom implementation but also holds strong potential for broader adoption through offline or mobile applications.